UJI KONSENTRASI BIOFUNGISIDA TEPUNG Trichoderma harzianum Rifai TERHADAP JAMUR Phytophthora palmivora Butl. PENYEBAB PENYAKIT BUSUK BUAH KAKAO PASCA PANEN - YETTI ELFINA; MUHAMMAD ALI; DELIMA SABATINY (Universitas Riau, 2017)
losses on cocoa is black pod disease (BPD) caused by Phytophthora palmivora Butl. Alternatif control of thedisease is using biocontrol agent such as Trichoderma harzianum Rifai formulated in a powder biofungicidewhich has to be applied in a right concentration. The research aims to observe the effect of biofungicidepowder of T. harzianum in some concentrations and obtain the best consentration to control P. palmivoracauses cocoa black pod disease. This research has been conducted at Plant Pathology Laboratory, AgricultureFaculty of Riau University from August to October 2015. The research was carried out experimentally usinga completely randomized design consisted of 7 treatments (0, 100, 200, 300, 400, 500 and 600 g/l) and 4replications. The research consisted of two phases: in vitro inhibition test to P. palmivora and in vivoapplication test of T. harzianum powder biofungicide. Data obtained were statistically analyzed usinganalysis of variance and continued with Duncan’s New Multiple Range Test (DNMRT) at 5% level. Theresults showed that the concentration of T. harzianum powder biofungicide at 500 g/l had a better ability toinhibit the growth of P. palmivora at in vitro test with an inhibition up to 45,00% and relatively able tocontrol P. palmivora causes cocoa black pod disease at in vivo test with disease intensity 31,25%.